On the Atlantic species of the genus Abyssianira Menzies, 1956 (Isopoda: Asellota: Paramunnidae) - Doti, Brenda L.; Roccatagliata, Daniel (Zootaxa, 2006)
Two new Atlantic species of the genus Abyssianira are described: A. acutilobi n. sp. and A. lingula n. sp. from off Argentine and Brazilian coasts, respectively. In order to facilitate comparisons the descriptions of two previously known Atlantic species, A. dentifrons Menzies, 1956 and A. argentenensis Menzies, 1962, are completed. Four groups of dorsolateral wart-like elevations are herein described for the first time. These “warts” are present in A. acutilobi, A. lingula and A. dentifrons and they seem to consist of agglutinated sand and detritus. The diagnosis of the genus Abyssianira is emended, and a dichotomous key for these four species is offered.